Application of Game-Based Learning to Improve Student Learning Outcomes at SDN 29 Pagar Alam - Fernanda, Zulki; Manto, Manto (Innovative: Journal Of Social Science Research, 2024)
This research was motivated by the lack of student learning outcomes that are, on average, below KKM, the lack of variation in the application of learning models by teachers that cause students to get bored quickly in lessons, and the lack of interaction between teachers and students. This problem can be overcome by using the application of game-based learning. The purpose of this study is to improve student learning outcomes. This type of research is called classroom action research, which is carried out in two cycles, consisting of four stages: planning, implementation, observation, and reflection. This research was conducted at SDN 29 Pagar Alam. The subjects of this study were IVA students in the class, totaling 21. Data collection techniques include observation, tests, and documentation. The collection tools are student learning test result data and student observation sheets. Student learning outcomes in successive learning according to the pre-cycle, cycle I, and cycle II comparison. Pre-cycle by 23.8%, then increased in cycle I by 52.3%, and then increased again in cycle II by 90.4%, so using Game-Based Learning can improve student learning outcomes. The driving factor of this research is the ability of teachers to manage classrooms well and the effective use of learning media to increase student focus on learning. At the same time, the inhibiting factors include noise from outside the school. However, this can be overcome by providing guidance, motivation, and more intensive diversion to students. It can be concluded that applying Game-Based Learning can improve student learning outcomes.